YOGA AS A CATALYST FOR ACHIEVING UNITED NATIONS SUSTAINABLE DEVELOPMENT GOALS: A COMPREHENSIVE REVIEW - Ranjith Kamal P (IJRDO-Journal of Applied Science, 2024)
Yoga, an ancient holistic system originating from India over five thousand years ago, represents a multifaceted approach to human wellbeing integrating physical, mental, emotional, and spiritual dimensions. Contemporary global challenges, including escalating mental health disorders, chronic non-communicable diseases, environmental degradation, and social inequities, necessitate innovative health and development strategies. This paper examines yoga’s potential as a transformative intervention for achieving the United Nations Sustainable Development Goals (SDGs). Through a comprehensive review of peer-reviewed literature, the study demonstrates that traditional yoga practices directly support multiple SDGs: SDG 3 (Good Health and Well-Being), SDG 4 (Quality Education), SDG 5 (Gender Equality), SDG 11 (Sustainable Cities and Communities), SDG 13 (Climate Action), and SDG 15 (Life on Land). The evidence indicates that yoga functions as both a preventive and therapeutic modality, promoting holistic development while promoting environmental consciousness and social cohesion. This paper argues for integrating yoga into healthcare systems, educational curricula, and public health policies as a cost-effective, accessible, and culturally sensitive intervention to support sustainable development objectives through 2030 and beyond.